2012
DOI: 10.1155/2012/935425
|View full text |Cite
|
Sign up to set email alerts
|

Role ofIn VitroStimulation with Lipopolysaccharide on T-Cell Activation in HIV-Infected Antiretroviral-Treated Patients

Abstract: We investigated the effect of LPS in vitro stimulation on T-cell activation in HIV-infected patients with different CD4+ recovery on HAART. PBMCs from 30 HIV-positive, HAART-treated, aviremic individuals with different CD4+ reconstitution (Low Responders: CD4+ < 350/μL; Intermediate Responders: CD4+ 350–599/μL; High Responders: CD4+ ≥ 600/μL) were cultured with LPS and the proportion of HLA-DR/CD38- and Ki67-expressing CD4+/CD8+ T-cells was measured (flow cytometry). Upon LPS stimulation, significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…In that study, in vitro exposure to microbial TLR ligands promoted the cell surface expression of lymphocyte-homing and activation/apoptosis molecules on CD4 ϩ and CD8 ϩ T cells (67). Consistent with those observations, in vitro stimulation by microbial and viral TLR ligands was shown to induce T-cell activation in both antiretroviral-naïve and ART-treated, HIV-infected patients (68,69). By extension, those in vitro findings suggested that systemic exposure to TLR ligands in HIV-infected patients results in heightened immune activation, effector T-cell sequestration in lymphoid tissues, and T-cell turnover, thus reinforcing the hypothesis that microbial translocation is a crucial determinant of immune activation.…”
Section: Microbial Translocation In the Pathogenesis Of Hiv And Siv Isupporting
confidence: 59%
“…In that study, in vitro exposure to microbial TLR ligands promoted the cell surface expression of lymphocyte-homing and activation/apoptosis molecules on CD4 ϩ and CD8 ϩ T cells (67). Consistent with those observations, in vitro stimulation by microbial and viral TLR ligands was shown to induce T-cell activation in both antiretroviral-naïve and ART-treated, HIV-infected patients (68,69). By extension, those in vitro findings suggested that systemic exposure to TLR ligands in HIV-infected patients results in heightened immune activation, effector T-cell sequestration in lymphoid tissues, and T-cell turnover, thus reinforcing the hypothesis that microbial translocation is a crucial determinant of immune activation.…”
Section: Microbial Translocation In the Pathogenesis Of Hiv And Siv Isupporting
confidence: 59%
“…T-cell activation (16)(17)(18), and have previously shown that its expression is low in CD4 + and CD8 + T cells during the acute phase of KD (20,28,29). This data was further corroborated by another research group, which observed that the number of HLA-DR + CD8 + T cells does not increase during the acute phase of KD (30).…”
Section: Discussionsupporting
confidence: 52%
“…Autopsy studies of children with KD who died during the acute phase clearly indicate that CD4 + and CD8 + T cells participate in the transmural infiltration of the coronary arterial wall (14). Notably, human leukocyte antigen-DR (HLA-DR), a cell-surface glycoprotein encoded by the HLA-DR region of the major histocompatibility complex (15), is a known marker of T-cell activation (16)(17)(18), but the function of this antigen on the different T-cell populations during KD is unknown. In this study, we have investigated the relationship between HLA-DR expression on peripheral CD4 + and CD8 + T cells, and thus the activation of these cells, and the response to IVIG treatment in children with KD.…”
mentioning
confidence: 99%
“…Along the same line, in vitro research has shown a direct link between microbial stimulation and immune activation in both HIV-uninfected (12, 3739, 53) and HIV-infected untreated individuals through TLR signaling (18, 31, 33, 50, 5961). …”
Section: Discussionmentioning
confidence: 97%
“…Besides, recent literature in both HIV-negative and HIV-positive individuals provided ex vivo evidence for a direct role of translocating microbial products in driving immune activation. In particular, ex vivo stimulation of PBMCs and antigen-presenting cells with bacterial ligands (including LPS), commensal bacteria, and combined bacterial and viral stimulus results in the production of pro- and anti-inflammatory cytokines (3650). In cART-treated patients, increased CD8+ CD38+ cells have been reported upon LPS exposure in subjects with poor CD4+ T-cell restoration (50) as well as impaired IFN-α production, following stimulation of plasmacytoid dendritic cells with TLR7 and TLR9 agonists (51).…”
Section: Introductionmentioning
confidence: 99%